Strengthening Teacher Engagement through POP-SDM Modeling: A Study of Permanent Teachers in Bogor Educational Foundation (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aimed to develop and validate a comprehensive model for strengthening teacher engagement through the application of the POP-SDM (Modeling and Optimization of Human Resource Management) method among permanent teachers at Bogor Educational Foundation. Method: The research employed a mixed-methods approach combining qualitative exploratory methods with quantitative causal analysis. The study involved 30 permanent teachers selected through random sampling. The qualitative phase utilized in-depth interviews to identify dominant factors influencing teacher engagement, while the quantitative phase employed path analysis to examine relationships between identified variables. The POP-SDM method was implemented through systematic modeling and optimization processes, integrating local wisdom values with organizational support structures. Results: Preliminary survey analysis revealed significant gaps in teacher engagement dimensions: 39% of teachers showed deficiencies in vigor (energy and resilience), 52% in dedication (sense of meaning and purpose), 43% in absorption (focus and immersion), 27% in commitment to school, 38% in collaboration with colleagues, and 36% in self-development. Path analysis identified four dominant factors influencing teacher engagement: organizational leadership, professional development opportunities, work environment support, and integration of local cultural values. The developed model demonstrated strong predictive validity for engagement enhancement. Novelty: This study introduces the innovative application of the POP-SDM method in educational management contexts, specifically for teacher engagement optimization. It provides an integrated framework that combines quantitative modeling with qualitative exploration, addressing the complex interplay between organizational structures and cultural values in educational settings. The research contributes to both theoretical understanding and practical strategies for enhancing teacher professionalism in Indonesian educational institutions.